Community-Specific BMI Cutoff Points for South Indian Females - K. B. Kishore Mohan; V. Sapthagirivasan; M. Anburajan (Journal of Obesity)
Objective. To analyze multiparameters related to total body composition, with specific emphasis on obesity in South Indian females, in order to derive community-specific BMI cutoff points. Patients and Methods. A total number of 87 females (of age 37.33±13.12 years) from South Indian Chennai urban population participated in this clinical study. Body composition analysis and anthropometric measurements were acquired after conducting careful clinical examination. Results. BMI demonstrated high significance when normal group (21.02±1.47 kg/m2) was compared with obese group (29.31±3.95 kg/m2), 𝑃<0.0001. BFM displayed high significance when normal group (14.92±4.28 kg) was compared with obese group (29.94 ± 8.1 kg), 𝑃<0.0001. Conclusion. Community-specific BMI cutoffs are necessary to assess obesity in different ethnic groups, and relying on WHO-based universal BMI cutoff points would be a wrong strategy.